Guilt, Shame, and Reparative Behavior: The Effect of Psychological Proximity - Ghorbani, Majid; Liao, Yuan; Çayköylü, Sinan; Chand, Masud (2013)
Research has paid scant attention to reparative behavior to compensate for unintended wrongdoing or to the role of emotions in doing the right thing. We propose a new approach to investigating reparative behavior by looking at moral emotions and psychological proximity. In this study, we compare the effects of moral emotions (guilt and shame) on the level of compensation for financial harm. We also investigate the role of transgressors’ perceived psychological proximity to the victims of wrongdoing. Our hypotheses were tested through a scenario based questionnaire on a sample of 261 participants. Analyses indicate that (1) guilt has a stronger effect on the level of compensation than shame; (2) psychological proximity influences the level of guilt, shame, and compensation; and (3) shame interacts with psychological proximity to predict compensation, whereas guilt mediates the relationship between psychological proximity and compensation.
Keywords: Unintended transgression; Reparative behavior; Psychological proximity; Shame; Guilt; Ethical decision making; Emotional ethics; Construal level theory